2015
DOI: 10.1097/igc.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Ovarian Epithelial Cancer in the Elderly

Abstract: Ovarian cancer prognosis is poorer for older women, but they are more frequently suboptimally treated. No correlation could be observed between geriatric factors and surgery or chemotherapy achievement. Treatment decision should be based on objective geriatric assessment in order to improve outcome in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 40 publications
1
30
1
2
Order By: Relevance
“…16 A recent case-control study, including patients aged 70 years or older and younger cases, showed that younger patients have a significantly longer median OS (65.2 vs 26.2 months). 6 Conversely, a prospective analysis of the ovarian cancer diagnosis consortium concluded that women aged 70 years or older were less likely to receive an optimal treatment compared with younger women, and their outcome was less favorable. However, age lost its prognostic relevance at multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…16 A recent case-control study, including patients aged 70 years or older and younger cases, showed that younger patients have a significantly longer median OS (65.2 vs 26.2 months). 6 Conversely, a prospective analysis of the ovarian cancer diagnosis consortium concluded that women aged 70 years or older were less likely to receive an optimal treatment compared with younger women, and their outcome was less favorable. However, age lost its prognostic relevance at multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the expression of the immune markers on OS was expressed using hazard ratios (HRs) with 95% confidence interval (CI), estimated using univariable and multivariable Cox regression. The multivariable analysis adjusted for clinical factors known to influence HGSC survival, age at diagnosis (≥ 70 vs. < 70), stage (IV vs. III), and residual tumor following primary cytoreductive surgery (macroscopic residual tumor vs. no) [1,26,27], were analyzed as binary factors. All P values are two sided.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Several observational studies have shown that elderly ovarian carcinoma patients receive standard treatment less frequently than their younger counterparts. This applies to both chemotherapy and CRS [3,[7][8][9][10][11]. Older patients less often have complete surgery [10] and suffer more frequently from postoperative complications and mortality [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This applies to both chemotherapy and CRS [3,[7][8][9][10][11]. Older patients less often have complete surgery [10] and suffer more frequently from postoperative complications and mortality [12][13][14]. A Dutch single-centre cohort study [15] found that 11 out of 47 patients (23%) aged 70 years or older who were considered fit for standard treatment, were not able to complete treatment without adjustments.…”
Section: Introductionmentioning
confidence: 99%